Cell derived extracellular matrix fibers synthesized using sacrificial hollow fiber membranes. (28th December 2017) - Roberts, Kevin; Schluns, Jacob; Walker, Addison; Jones, Jake D; Quinn, Kyle P; Hestekin, Jamie; Wolchok, Jeffrey C
Abstract: The therapeutic potential of biological scaffolds as adjuncts to synthetic polymers motivates the engineering of fibers formed using the extracellular matrix (ECM) secreted by cells. To capture the ECM secreted by cells during in vitro culture, a solvent degradable hollow fiber membrane (HFM) was created and utilized as a cell culture platform. NIH/3T3 fibroblasts were injected into the narrow (0.986 ± 0.042 mm) lumina of mesoporous polysulfone HFMs and maintained in culture for up to 3 weeks. Following cell culture, HFMs were dissolved using N-methyl-2-pyrrolidone and the accumulated ECM was collected. The ECM retained the filamentous dimensions of the HFM lumen. The process yielded up to 0.89 ± 0.20 mg of ECM for every mm of HFM dissolved. Immunofluorescence, second-harmonic generation microscopy, and tandem mass spectrometry indicated the presence of an array of ECM constituents, including collagen, fibronectin, and proteoglycans, while FTIR spectra suggested thorough HFM material dissolution. Isolated ECM fibers, although fragile, were amenable to handling and exhibited an average elastic modulus of 34.6 ± 15.3 kPa, ultimate tensile strength of 5.2 ± 2.2 kPa, and elongation-at-break of 29% ± 18%. ECM fibers consisted of an interconnected yet porous (32.7% ± 5.8% open space) network which supported the attachment and in vitro proliferation of mammalian cells. ECM fibers were similarly synthesized using muscle and astrocyte cells, suggesting process robustness across different cell types. Ultimately, these ECM fibers could be utilized as an alternative to synthetics for the manufacture of woven meshes targeting wound healing or regenerative medicine applications.